2015
DOI: 10.3390/nu7020831
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Eleutherine americana-Alginate Complex Microcapsules and Application in Bifidobacterium longum

Abstract: Microencapsulation using extrusion and emulsion techniques was prepared for Bifidobacterium longum protection against sequential exposure to simulated gastric and intestinal juices, refrigeration storage and heat treatment. Eleutherine americana was used as the co-encapsulating agent. Hydrolysis of E. americana by gastric and intestinal juices was also determined. E. americana and its oligosaccharide extract demonstrated their resistance to low pH and partial tolerance to human α-amylase. Microencapsulated B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…Casein-based microencapsulation proved to improve the viability of Lactobacillus F19 and Bifidobacterium Bb12 during freeze drying and subsequent storage [163]. Phoem, et al [164] microencapsulated B. longum using extrusion and emulsion techniques for protection against sequential exposure to simulated gastric and intestinal juices, refrigeration storage and heat treatment. These results showed that encapsulated B. longum with Eleutherine americana and oligosaccharide extract prepared by the extrusion technique, survived better than that by the emulsion technique under adverse conditions.…”
Section: Strategies For Enhanced Probiotic Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Casein-based microencapsulation proved to improve the viability of Lactobacillus F19 and Bifidobacterium Bb12 during freeze drying and subsequent storage [163]. Phoem, et al [164] microencapsulated B. longum using extrusion and emulsion techniques for protection against sequential exposure to simulated gastric and intestinal juices, refrigeration storage and heat treatment. These results showed that encapsulated B. longum with Eleutherine americana and oligosaccharide extract prepared by the extrusion technique, survived better than that by the emulsion technique under adverse conditions.…”
Section: Strategies For Enhanced Probiotic Viabilitymentioning
confidence: 99%
“…These results showed that encapsulated B. longum with Eleutherine americana and oligosaccharide extract prepared by the extrusion technique, survived better than that by the emulsion technique under adverse conditions. The viability of encapsulated cells was better than free cells at 65 °C for 15 min [164].…”
Section: Strategies For Enhanced Probiotic Viabilitymentioning
confidence: 99%
“…Microencapsulation generally leads to increased survival of LAB and Bifidobacterium spp. under artificial GIT conditions, as compared to free cells [13,37,38]. Reduced survival of cells in SGJ without pepsin and pancreatin may be due to the lower pH (1.5) of SGJ without pepsin in comparison with that of SGJ with pepsin (pH 2.5).…”
Section: Discussionmentioning
confidence: 97%
“…Several materials viz. carrageenan, pectin, whey proteins and chitosan [23,37] have been successfully employed for microencapsulation of probiotics. Microencapsulation generally leads to increased survival of LAB and Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an E. americana oligosaccharide extract has been used as a prebiotic that stimulates growth of the intestinal microbiota [10]. E. americana oligosaccharide extract has demonstrated resistance to low pH and partial tolerance to human α-amylase [13]. It has been previously found that encapsulation of Bifidobacterium longum with E. americana oligosaccharide extract increased its survival in simulated gastrointestinal conditions [13], in fresh milk tofu, and in pineapple juice [14].…”
Section: Introductionmentioning
confidence: 99%